2019
DOI: 10.1177/1479164119878427
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine transporter 2 is involved in high glucose-induced damage and altered thiamine availability in cell models of diabetic retinopathy

Abstract: Thiamine prevents high glucose-induced damage in microvasculature, and progression of retinopathy and nephropathy in diabetic animals. Impaired thiamine availability causes renal damage in diabetic patients. Two single-nucleotide polymorphisms in SLC19A3 locus encoding for thiamine transporter 2 are associated with absent/minimal diabetic retinopathy and nephropathy despite long-term type 1 diabetes. We investigated the involvement of thiamine transporter 1 and thiamine transporter 2, and their transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 40 publications
7
19
1
Order By: Relevance
“…Starting from these assumptions, our aims were to investigate the modulation of thiamine transporter expression in renal cells involved in DN and exposed to conditions mimicking the diabetic microenvironment, such as glucose fluctuations and thiamine deficiency, and if these variations could influence thiamine uptake and transketolase activity, ultimately worsening DN. Our results confirmed that THTR2 is the thiamine transporter more involved in DN, as we already demonstrated in DR [3], and that lack of thiamine concurs with hyperglycemia in impairing thiamine transport.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Starting from these assumptions, our aims were to investigate the modulation of thiamine transporter expression in renal cells involved in DN and exposed to conditions mimicking the diabetic microenvironment, such as glucose fluctuations and thiamine deficiency, and if these variations could influence thiamine uptake and transketolase activity, ultimately worsening DN. Our results confirmed that THTR2 is the thiamine transporter more involved in DN, as we already demonstrated in DR [3], and that lack of thiamine concurs with hyperglycemia in impairing thiamine transport.…”
Section: Introductionsupporting
confidence: 91%
“…Relative gene expression was determined using the 2 −∆∆CT method and normalized against β-actin. Primers used were: THTR1 forward: 5 -AGCCAGACCGTCTCCTTGTA-3 , reverse: 5 -TAGAGAGGGCCCACCACAC-3 ; THTR2 forward: 5 -CTGGCTCTGGTGGTCTTCTC-3 , reverse: 5 -AGGCATAGCGTTCCACATTC-3 ; Sp1 forward: 5 -TGCAGCAGAATTGAGTCACC-3 , reverse: 5 -CACAACATACTGCCC-ACCAG-3 [3]; TK forward: 5 -CCCAGCTACAAAGTTGGGGACAAG-3 ; reverse, 5 -GGTCATCCTTGCTCTTCAGGACC-3 .…”
Section: Localization Of Thiamine Transporters Thtr1/2 and Sp1mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most significant DMPs (cg07417745) is located in intron 1 of the SLC19A3 gene, which encodes a thiamine transporter [20], and showed a linear relationship between increased DNA methylation and the number of LG exposures. Interestingly, expression of this gene has previously been found to be modulated by hyperglycaemic-like conditions [21]. Conversely, methylation of cg11022541 and cg11692715 located within the genes NIPA1 and SLC8B1 respectively, decreased following RLG.…”
Section: Discussionmentioning
confidence: 93%